IEEE 2002 28th Annual Conference of the Industrial Electronics Society. IECON 02
DOI: 10.1109/iecon.2002.1185403
|View full text |Cite
|
Sign up to set email alerts
|

Operation of single-phase induction motor as two-phase motor

Abstract: In this paper, it is proposed to drive a single-phase induction motor with a two-phase supply. The two-phase supply is obtained from the conventional single-phase utility supply by using a two-phase inverter. The adverse effects of most of the harmonics associated with the use of the two-phase inverter are alleviated by cancelinglattenuating the dominant harmonics in the motor terminal voltages using the selective harmonic elimination (SHE) pulse width modulation (PWM) technique.. The performance of the motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…For the one-phase motor parameters given in Appendix A, it was shown that, at the same value of steady-state slip, the motor produces 23.4% more power when operated in Downloaded by [University of Nebraska, Lincoln] at 09:46 03 January 2015 the two-phase mode of operation [1]. In other words, for a 1.5-hp one-phase IM operated in the two-phase mode, the new motor output power becomes P out D 1:234 1:5 D 1:851 hp D 1:3801 kW: (8) Referring to Figure 1, the motor output power can be written as…”
Section: Variable-speed Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the one-phase motor parameters given in Appendix A, it was shown that, at the same value of steady-state slip, the motor produces 23.4% more power when operated in Downloaded by [University of Nebraska, Lincoln] at 09:46 03 January 2015 the two-phase mode of operation [1]. In other words, for a 1.5-hp one-phase IM operated in the two-phase mode, the new motor output power becomes P out D 1:234 1:5 D 1:851 hp D 1:3801 kW: (8) Referring to Figure 1, the motor output power can be written as…”
Section: Variable-speed Operationmentioning
confidence: 99%
“…With the motor reactive power provided by the inverter, the PV array has to supply only the active power required by the motor [16]. Thus, for a motor output of 1380.9 W, and an overall motor efficiency of 84% [1], the motor input active power is given by P ac D 1380:9 0:84 D 1643:9 W:…”
Section: Sizing the Pv Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…1), thus allowing the use of a lower frame size to drive the same load. Running costs have been reduced by reducing the motor losses and improving its power factor, thus enhancing the motor efficiency [8].…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in increased torque harmonics as well as reduced motor overall efficiency. To alleviate such problem, a phase difference angle (PDA) control employing the pulsewidth modulation (PWM) selective harmonic elimination technique has been reported in [3] Manuscript received September 6, 2006 Torque-speed characteristics are improved when the single-phase IM is operated as an unsymmetrical two-phase motor [8].…”
Section: Introductionmentioning
confidence: 99%